Drug-drug interactions between Atorvastatin and Dronedarone mediated by monomeric CYP3A4 - Denisov, Ilia G. (Biochemistry, 2017)
Heterotropic interactions between atorvastatin (ARVS) and dronedarone (DND) have been deciphered using global analysis of the results of binding and turnover experiments for pure drugs and their mixtures. The in vivo presence of atorvastatin lactone (ARVL) was explicitly taken into account by using pure ARVL in analogous experiments. Both ARVL and ARVS inhibit DND binding and metabolism, while significantly higher affinity of CYP3A4 towards ARVL makes the latter the main effector in this system. Molecular dynamics simulations reveal significantly different modes of interactions of DND and ARVL with the substrate binding pocket and with the peripheral allosteric site. Interactions of both substrates with residues F213 and F219 at the allosteric site play the most important role in the communication of conformational changes induced by effector binding towards productive binding of substrate at the catalytic site.